Computer-assisted quantification and visualization of bowel perfusion using fluorescence-based enhanced reality in left-sided colonic resections - D’Urso, Antonio; Agnus, Vincent; Barberio, Manuel; Seeliger, Barbara; Marchegiani, Francesco; Charles, Anne-Laure; Geny, Bernard; Marescaux, Jacques; Mutter, Didier; Diana, Michele (Surgical endoscopy, 2021)
Background Fluorescence-based enhanced reality (FLER) is a computer-based quantification method of fluorescence angiographies to evaluate bowel perfusion. The aim of this prospective trial was to assess the clinical feasibility and to correlate FLER with metabolic markers of perfusion, during colorectal resections. Methods FLER analysis and visualization was performed in 22 patients (diverticulitis n = 17; colorectal cancer n = 5) intra- and extra-abdominally during distal and proximal resection, respectively. The fluorescence signal of indocyanine green (0.2 mg/kg) was captured using a near-infrared camera and computed to create a virtual color-coded cartography. This was overlaid onto the bowel (enhanced reality). It helped to identify regions of interest (ROIs) where samples were subsequently obtained. Resections were performed strictly guided according to clinical decision. On the surgical specimen, samplings were made at different ROIs to measure intestinal lactates (mmol/L) and mitochondria efficiency as acceptor control ratio (ACR). Results The native (unquantified) fluorescent signal diffused to obvious ischemic areas during the distal appreciation. Proximally, a lower diffusion of ICG was observed. Five anastomotic complications occurred. The expected values of local capillary lactates were correlated with the measured values both proximally (3.62 ± 2.48 expected vs. 3.17 ± 2.8 actual; rho 0.89; p = 0.0006) and distally (4.5 ± 3 expected vs. 4 ± 2.5 actual; rho 0.73; p = 0.0021). FLER values correlated with ACR at the proximal site (rho 0.76; p = 0.04) and at the ischemic zone (rho 0.71; p = 0.01). In complicated cases, lactates at the proximal resection site were higher (5.8 ± 4.5) as opposed to uncomplicated cases (2.45 ± 1.5; p = 0.008). ACR was reduced proximally in complicated (1.3 ± 0.18) vs. uncomplicated cases (1.68 ± 0.3; p = 0.023). Conclusions FLER allows to image the quantified fluorescence signal in augmented reality and provides a reproducible estimation of bowel perfusion (NCT02626091).